Transapical Endovascular Repair of an Ascending Aortic Pseudoaneurysm. Issue 7 (17th May 2016) - Howell, Eric; Sweet, Matthew P.; Pal, Jay D.
Abstract: Proximal aortic pathology provides a technical challenge for endovascular repair. We present a case of successful transapical endovascular aortic repair in a patient with a proximal suture line pseudoaneurysm who was not a candidate for open surgical repair. doi: 10.1111/jocs.12766 (J Card Surg 2016;31:456–460)